KONFLIK DALAM ORGANISASI DAN NEGOSIASI - Mutya Istikarani; Lisariyadi; Sukatin; Zulqarnain (PT. Hasba Edukasi Mandiri, 2025)
This paper aims to examine the dynamics of conflict within organizations and the negotiation strategies that can be applied to manage and resolve such conflicts. The method used in this study is library research, involving the collection, review, and analysis of various relevant scholarly sources such as books, journals, and previous research articles. The findings indicate that organizational conflict is an inevitable phenomenon, often arising from differences in interests, values, communication, and organizational structures. Conflict can have both negative and positive impacts, depending on how it is managed by the organization. In this context, negotiation emerges as a key approach to achieving constructive conflict resolution. Effective negotiation strategies—such as collaboration, compromise, and win-win approaches—have proven to reduce tensions and enhance relationships among individuals and groups within organizations. Therefore, a deep understanding of conflict and negotiation techniques is crucial for the development of adaptive and harmonious organizational management.